Infrastructural immobility: movement and material culture in the Calais Jungle - Scott-Smith, T (SAGE Publications, 2022)
This paper develops the idea of infrastructural immobility, a dynamic within infrastructural systems whereby the movement of one thing relies upon the immobility of another. Drawing on fieldwork carried out in the Calais Jungle over the summer of 2016, it explores the relationship between what moves and what stays in processes of migration, arguing that if we are to make sense of camps as both spaces of confinement and spaces of mobility it is important to look at the role of infrastructures and the objects they contain. Infrastructures have been defined as ‘matter that enables the movement of other matter’ but it is rarely acknowledged that the matter that facilitates movement will often have to stay immobile. To carry cars, our roads need to stay fixed: they must not shift, rupture, buckle or break. To channel water, pipes need to be sealed and secured, remaining stationary and solid. This also applies to camps and other carceral junctions, which have their own balance of confinement and mobility shaped by material forms. This paper focuses on two objects in Calais – fencing and shipping containers – to illustrate the point.